Water resources and the historic wells of Barbuda: tradition, heritage and hope for a sustainable future - Rebecca Boger; Sophia Perdikaris; Amy E. Potter; John Mussington; Reginald Murphy; Louise Thomas; Calvin Gore; Dwight Finch (Island Studies Journal, 2014)
The island of Barbuda has a relatively unique history, land tenure and geography. Unlike its Caribbean counterparts, the island is not suited to large-scale agriculture due to its arid climate and relatively thin soils. Instead, the enslaved and eventually free people of Barbuda developed a complex herding ecology centered on common land ownership. As a result, carefully designed historic wells are strategically located around the island. With the challenges brought about by climate change, an interdisciplinary, international team led by the Barbuda Research Complex is investigating the state of existing water and food resources and examining how the availability and quality of water resources have influenced local cultural practices. Barbudans and international scientists are working together to improve their resilience and live more sustainably in this new era of climatic adversity.